Matlab Applications for Skew-Symmetric Matrices and Integral Curves in Lorentzian Spaces - Tuhahan Turhan; Y.Emre Göktepe; Nihat Ayyıldız (Düzce Üniversitesi Bilim ve Teknoloji Dergisi)
In [8], the authors obtained the non-zero solutions of the equation A(x)=0, in Lorentzian space where A is a skew-symmetric matrix corresponding to the linear map A and got normal forms of the skew-symmetric matrix A, depending on the causal characters of the vector x. Taking into consideration the structure of the matrix A, we generate Matlab codes and make some Matlab applications for normal form of skew-symmetric matrix. Also, we give some Matlab codes for the linear first order system of differantial equations which the solution of the system gives rise to integral curves of linear vector fields in such a space. Moreover, we give some application with respect to special case of n and causal characters of the vector x for Matlab.